Efficient Photocatalytic Hydrogen Evolution by Modulating Excitonic Effects in Ni‐Intercalated Covalent Organic Frameworks. Issue 13 (15th February 2023) - Shen, Rongchen; Li, Xiuzhi; Qin, Chaochao; Zhang, Peng; Li, Xin
Abstract: Covalent organic frameworks (COFs) as appealing platforms have received tremendous interest in the field of photocatalytic H2 evolution owing to their well‐defined structures and tailor‐made function. However, excitonic effects resulting from Coulomb interactions between electron–hole pairs are key rate‐determining processes in photocatalytic hydrogen evolution, which are usually ignored. Thus, it is of profound significance and highly desired, but it is still a challenge, to explore new routes to modulate excitonic dissociation in COFs for boosting photocatalysis. To address this challenge, Ni‐intercalated fluorenone‐based COFs (Ni‐COF‐SCAU‐1) at the imine linkage, are proposed for the first time, and demonstrated to exhibit the enhanced polarization electric field; thus, facilitating the Hall electron mobility and the dissociation of singlet excitons into free charge carriers under photoexcitation to participate in the surface hydrogen evolution reaction. Benefiting from these results, Ni‐COF‐SCAU‐1 displays a hydrogen production rate of 197.46 mmol·g −1 h −1 under visible light irradiation with an apparent quantum efficiency (AQE) up to 43.2% at 420 nm. This work offers an in‐depth understanding of the crucial role of the interlayer atomic interface in improving photocatalytic hydrogen evolution and paves a new way for excitonic regulation in the COFs. Abstract : Ni‐intercalated fluorenone‐based covalent organic frameworks (COFs) at the imine linkage, are proposed for the first time, whose high photocatalytic H2 ‐evolution activity benefits from the improved Hall electron mobility and dissociation of singlet excitons into free charge carriers, originating from the enhanced polarization electric fields. The concept of intercalating Ni in COFs provides an innovative method to achieve efficient photocatalysis.